Handlist of Arabic Manuscripts (New Series) in the Princeton University Library - Mach, Rudolf 1922-1981 (Princeton Studies on the Near East, 2017)
This catalogue describes over 2,000 Arabic manuscripts acquired by the Princeton University Library since the 1950s, providing information on an important collection of Arabic works, many of which were previously unknown or unrecorded.Originally published in 1987.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905